2022
DOI: 10.1002/ardp.202200048
|View full text |Cite
|
Sign up to set email alerts
|

New quinoxalin‐2(1H)‐one‐derived VEGFR‐2 inhibitors: Design, synthesis, in vitro anticancer evaluations, in silico ADMET, and docking studies

Abstract: More than 70% of cancer patients who are treated with chemotherapeutics do not show a durable response. As part of the global plan seeking new effective chemotherapeutics, here, we report the synthesis and in vitro and computational studies of new lenvatinib and sorafenib analog quinoxalines as vascular endothelial growth factor receptor II (VEGFR-2) tyrosine kinase inhibitors. The central quinolone and pyridine moieties of the Food and Drug Administration-approved anticancer agents lenvatinib and sorafenib we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…The cytotoxic activity was assessed using the MTT colorimetric assay as reported previously. [58][59][60][61][62] In brief, tumour cell lines were suspended in medium at concentration 5 Â 10 4 cell/well in Corning® 96-well tissue culture plates and then incubated for 24 h. The tested compounds with concentrations ranging from 0 to 50 mg ml À1 were then added into 96-well plates (in a triplicate) to achieve different concentrations for each compound. Vehicle controls with media or 0.5% DMSO were run for each 96 well plate as a negative control.…”
Section: Biological Evaluation Studiesmentioning
confidence: 99%
“…The cytotoxic activity was assessed using the MTT colorimetric assay as reported previously. [58][59][60][61][62] In brief, tumour cell lines were suspended in medium at concentration 5 Â 10 4 cell/well in Corning® 96-well tissue culture plates and then incubated for 24 h. The tested compounds with concentrations ranging from 0 to 50 mg ml À1 were then added into 96-well plates (in a triplicate) to achieve different concentrations for each compound. Vehicle controls with media or 0.5% DMSO were run for each 96 well plate as a negative control.…”
Section: Biological Evaluation Studiesmentioning
confidence: 99%
“…Furthermore: they may show reduced side effects. Accordingly, in this work, in continuation of our recent studies on the development of new suggested anticancer agents, [29][30][31][32][33][34][35] we considered the biological significance of VEGFR-2 inhibition as an effective strategy in the management of cancer and the importance of 1,2,3-triazole, thiazole, thiazolone, and hydrazine as attractive pharmacophoric fragments in the development of chemotherapeutic agents to design a new set of 1,2,3triazole hybrids as potential anticancer agents (Fig. 2).…”
Section: Rational and Aim Of This Workmentioning
confidence: 99%